Utilization of the use of technological devices in delivering communication information in the learning process - Irsyad, Irsyad; Anisah, Anisah; Ramadhan, Iwan; Lumbantoruan, Jitu Halomoan (Institute of Advanced Engineering and Science, 2024)
The development of increasingly sophisticated technology today brings education to participate in using the features available in today’s media such as the transition from face-to-face learning communication in schools to face-to-face assisted by technology such as laptops, tablets, cellphones and other multimedia. Technology currently provides innovation in the learning process both from home and from school. However, there are still many teachers and students who have not utilized technology such as laptops, tablets, cellphones and other multimedia in the learning process. The purpose of the study was to analyze the benefits and relationships of the four main variables of communication assessment elements with digital devices. The research method used was quantitative with a sample of 148 teachers randomly selected from schools that use technology in the learning process. Data collection techniques with instruments. The instruments used were four indicator instruments, namely technology from laptops, tablets, cellphones and other multimedia. Data analysis techniques with descriptive statistics using SPSS version 26.0 calculated the mean, standard deviation, and correlation test. The results of the study found that the four indicators had high reliability and the four indicators had significant utilization, were mutually positive and had a high relationship with each other. The conclusion is that the four technological devices are good for use in digital communication during the learning process and laptops and tablets are more recommended in this study.